India’s Foreign Trade With China: A Historical Showcase - Gupta, Deepa; Garg, A. K (Journal of Commerce and Trade, 2007)
India always had a surplus with the whole world including Europe, which was settled by the inflow of gold into India. But there was a steep decline in trade in the subsequent years since 1800 BC when the Aryans were ravishing most of Asia. In a variety of industries, cheap imports from China are killing local manufacturers. It needs probe as to how much profit is due to China’s competitiveness and how much due to dumping. With the advent of globalisation, liberalisation and reduction in trade import and export barriers the world has today become a tiny village. There are vast opportunities for increasing the contents of our export basket to China. The government in China, unlike that in India, is motivated to support economic activity. So, the government often enables entrepreneurship in China. Two-way trade between China and India rose to $24 billion in 2005 from $3 billion in 1999. Both countries have also become more important to each other’s trade. In 1999, China was India’s 13th most important import source and 17th as an export destination, but by 2005 China had risen to third in both. Although India does not rank quite as highly in China’s list of trading partners, it too has risen in importance, to 16th.